PENGARUH PEMANFAATAN INTERNET TERHADAP HASIL BELAJAR EKONOMI KELAS XI DI SMA NEGERI 10 PONTIANAK - Shafira Nur; Achmadi Achmadi; Husni Syahrudin (Universitas Tanjungpura, 2020)
Abstract This study aims to determine the effect of internet utilization on the learning outcomes of students of class XI IPS SMA Negeri 10 Pontianak. The research method used is descriptive quantitative research. The source of the data in this study were 50 XI IPS students. The results of the study indicate that there is an influence on the use of internet in class XI IPS SMA Negeri 10 Pontianak. Based on the calculation of hypothesis testing that there is a significant positive effect, which is indicated. With a simple linear regression calculation, the equation Y = 36.493 + 0.300X is obtained. The magnitude of the effect of variable X on variable Y (coefficient of determination) is 0.279. Which means that the percentage of internet utilization on the learning outcomes of students of class XI IPS in economics is 27.9% while the rest is influenced by other variables. Therefore it is concluded in general that the use of internet class XI IPS SMA Negeri 10 Pontianak is included in the good category. It can be seen from the completeness of student learning by 76%.Keywords: Internet Utilization, Economic Learning, Learning Outcomes